Methicillin-resistant Staphylococcus aureus (MRSA) nasal carriage among patients with diabetes at the Korle Bu Teaching Hospital. - Ramzy B Anafo (Public Library of Science (PLoS), 2021)
Aim To investigate the epidemiology of S. aureus and MRSA nasal carriage among people with diabetes at the Korle Bu Teaching Hospital in Accra, including the prevalence, predictors of carriage, and antibiotic resistance. Methodology This study was cross-sectional, involving 300 diabetes patients and 106 non-diabetic individuals. Swab specimens of the nares were obtained from the participants and bacteriologically-cultured. Identification and characterization of S. aureus and MRSA were based on standard bacteriological methods; antimicrobial susceptibility testing was by the Kirby-Bauer method. Results The prevalence of staphylococcal carriage, the diabetes group relative to the non-diabetes group, were 31.0% and 10.4% (S. aureus), and 3.3% and 0.0% (MRSA). Presence of diabetes predisposed to S. aureus carriage, but not MRSA nor coagulase-negative staphylococci (CoNS) carriage (OR = 3.88; p < 0.0001). Colonization with CoNS was protective of S. aureus (OR = 0.039, p < 0.001) and MRSA (OR = 0.115, p = 0.043) colonization among the diabetics. The antimicrobial resistance patterns recorded among the S. aureus isolated from the diabetic individuals relative to the non-diabetics were as follows: penicillin (95% vs. 91%), tetracycline (37% vs. 27%), cotrimoxazole (30% vs. 36%), erythromycin (17% vs. 0%), norfloxacin (13% vs. 0%), clindamycin (12% vs. 0%), gentamicin (9% vs. 0%), fusidic acid (10% vs. 9%), linezolid (4% vs. 0%), and rifampicin (5% vs. 0%). The proportion of multidrug resistant S. aureus was 41% (n = 38) in the diabetes group and 0% in the non-diabetes group; this difference was statistically significant (p = 0.01). Conclusions The presence of diabetes predisposed the participants to S. aureus carriage by almost four folds, but not MRSA carriage. Colonization with CoNS was protective of S. aureus and MRSA carriage in the diabetes group. Finally, linezolid remains a good therapeutic agent for anti-MRSA therapy.